Association between serum vitamin D metabolites and metabolic function in healthy Asian adults - Ding, Cherlyn (2021)
The association between low vitamin D status and the development of type 2 diabetes mellitus is well established; however, intervention trials that increased serum vitamin D (through ultraviolet B exposure or dietary supplementation) provide mixed outcomes. Recent evidence suggests that metabolites directly related to vitamin D receptor activation—1α,25-dihydroxyvitamin D3 and 24R,25-dihydroxyvitamin D3—may be better markers of vitamin D repletion status. We tested the hypothesis that a vitamin D metabolite (VDM) index, calculated as the sum of normalized fasting serum concentrations of 1α,25-dihydroxyvitamin D3 and 24R,25-dihydroxyvitamin D3, is associated with metabolic function. We measured subcutaneous and visceral adipose tissue volume, intrahepatic triglyceride content, maximum oxygen uptake, insulin sensitivity (4 h hyperinsulinemic-euglycemic clamp), and insulin secretion (3 h meal tolerance test with mathematical modeling) and calculated the VDM index in 65 healthy Asian adults. Subjects with a low VDM index had lower peripheral insulin sensitivity and beta-cell function compared to subjects with a high VDM index (both p < 0.05), matched for age, sex, BMI, and serum 25-hydroxyvitamin D3. Serum 25-hydroxyvitamin D3 was not associated with peripheral insulin sensitivity or beta-cell function. Our results suggest that, rather than enhancing vitamin D substrate availability, upregulation of vitamin D action is more likely to lead to improvements in glucose homeostasis.